Clinical Manifestations of the Gastrointestinal System in Patients with SARS-CoV-2 Infection - Kharizmatika Kharizmatika; Judya Sukmana; Roostantia Indrawati; Christian Bambang Sulistio (Universitas Malahayati, 2024)
ABSTRACT SARS-CoV-2 infection was declared as a pandemic by the WHO since March 11, 2020, with confirmed cases increasing every year. SARS-CoV-2 is one of the varian of coronavirus that has a higher transmission rate, where it is transmitted through infected droplets. SARS-CoV-2 can manifest in the digestive tract. This descriptive study uses a literature study method. Diarrhea was a common symptom of gastrointestinal manifestations in COVID-19 patients. Apart from diarrhea, other symptoms are anorexia, nausea, vomiting and abdominal pain. Gender prevalence varies. The average age of patients exposed to COVID-19 was over 50 years with hypertension as the most common comorbidity. SARS-CoV-2 are associated with Gastrointestinal manifestations which binds to ACE2 on gastrointestinal epithelial cells. SARS-CoV-2 infection causes an imbalance in the gut microbiota that can trigger secondary infections and multiple organ disorders and affect the severity of COVID-19. Keywords: COVID-19, Gastrointestinal Symptoms, ACE2, Gut Microbiota, Gut-Lung Axis